Evolução e distribuição do conhecimento sobre responsabilidade social corporativa: análise cientométrica - Araújo, Gabriel Aguiar de (2017)
The central issue that permeates human development is the ability to store and share the knowledge generated, since it underlies all decisions made by humans. Thus, humanity is perfected, expanding the horizons of the possible experiences every generation and then, knowledge inexorably grows and evolves too. This work is adhered to scientific knowledge, which is knowledge generated through techniques and specific criteria and is based on theories. More specifically, about the knowledge about Corporate Social Responsibility (CSR). Its objective was to evaluate the evolution and quantitative distribution of knowledge about CSR in terms of its (scientific) intellectual structure. A bibliometric and scientometric study was carried out on this field of knowledge. The findings allowed a general overview of the field, indicating its tendencies and main actors.